Potential of Halal Industry in South Sulawesi Province: An Analysis of Opportunities, Challenges, And Strategies - Ilyas, Muh. Indra Fauzi; Syamsuri, Helmy; Siradjuddin (The Institute of Academic Research and Publication (IARP), 2024)
The phenomenon of globalization of the halal industry has become an important issue that needs to be considered by Islamic economic practitioners. This is not only about meeting the needs and compliance of Muslims with sharia principles but also about becoming a globally recognized standard. This research aims to provide a comprehensive overview of the potential development of the halal industry in South Sulawesi Province and its development strategies so that the results of the research can be a reference for the government and stakeholders in developing the halal industry in South Sulawesi Province. This research used a descriptive qualitative approach. Secondary data was obtained from various sources, including books, journals, articles, data reports, and other relevant scientific sources. The results showed that the halal industry in South Sulawesi Province has a significant role, not only limited to the food and beverage sector. The halal industry has penetrated the Islamic finance sector, Muslim fashion, cosmetics, pharmaceuticals, travel, hotels, and tourism. Another reason for developing the halal industry's potential is that most of South Sulawesi's population is Muslim. In addition, the halal industry development strategy in South Sulawesi Province is by the development of world conditions and the direction of economic transformation as part of global participation, which is possible that South Sulawesi Province will become the leader of the halal industry in Indonesia.